Work alienation as a mediator between work from home-related isolation, loss of task identity and job insecurity amid the COVID-19 pandemic. Issue 3 (11th February 2022) - Mehta, Prashant
Abstract : Purpose: This sudden disruption of work in the world due to the coronavirus disease 2019 (COVID-19) pandemic has led to unravelling situations hitherto unknown to researchers and therefore requires careful and thorough investigation. The aim of the study was to investigate the relationship between work from home (WFH) isolation, WFH loss of task identity and job insecurity amid COVID-19 pandemic WFH arrangements by focusing on information technology/information technology-enabled services (IT/ITES) sector employees in India. The study also investigated the mediating role of work alienation. Design/methodology/approach: Data were collected from IT/ITES sector employees who were working from home. The sample size was 312, with 71.8% males and 28.2% females. The study used a descriptive research design. Analysis of the data was carried out using partial least square structural equation modeling. All constructs–independent and dependent–were reflectively measured. The evaluated quality parameters (discriminant validity, reliability, collinearity, common method bias) for all the constructs were found to be within acceptable limits. Findings: Findings from the study indicate that WFH-related isolation and loss of task identity have a significant direct impact on job insecurity. These, along with the mediating construct of work alienation, predicted a 35.8% variance in job insecurity. The study found that work alienation provided complementary mediation between the independent constructs evaluated. Originality/value: This study attempts to scrape the surface and gain insight into the problems that may arise in the new world of work. This paper presents an attempt to explain some of the psychological pitfalls associated with WFH during the COVID-19 pandemic and to understand their impact on job insecurity.